Arbovirus studies in Luanda, Angola: 1. Virological and serological studies during a yellow fever epidemic - Pinto, Manuel R. (1973)
A yellow fever epidemic broke out in Luanda, Angola, in January 1971 and was halted in less than 3 months by prompt mass vaccination and intensive antimosquito measures. Nine strains of yellow fever virus were isolated from hospitalized cases, but attempts to isolate the virus from Aedes aegypti mosquitos failed. A serological survey for antibodies to arboviruses in 589 sera from unvaccinated persons showed that two arboviruses were circulating in the epidemic area: the yellow fever virus and the Chikungunya virus responsible for an outbreak of dengue-like disease that occurred shortly before the yellow fever epidemic.